Penentuan Persamaan Kualitas Permukaan Bendakerja Hasil Proses Perautan Dengan Mesin Bubut Cnc. - Wirawan* _ (Politeknik Negeri Jakarta, 2010)
Determination of equation on surface quality of the workpiece which is produced by cutting process using cnc turning machine The problem is situated on the difficulties of predicting the surface roughness of the machined product using CNC turning machine, due to there is no mathematical model which expresses the surface formation on the cutting process. The objectives of this research is not only to observe the influence of cutting parameters to the surface rougness of the workpiece which is produced by machining process using CNC turning machine, but also to construct a mathematical model for predicting the surface roughness of the workpiece as a result of machining process with the cutting parameters involved. The research is carried out by: material selection of the test piece, test piece preparation, machining of the material test piece involving the predefined cutting data, and measuring oh the surface roughness of the work piece resulting from machining process. The result of this research is a surface roughness of the work piece which is machined using combination of cutting speed of 62.8; 141; 219 meter per menit, feedrate of 0.08; 0.34; 0.6 milimeter per rotation, and depth of cut of 0.08; 0.34; 0.6 milimeter. Finally, it is identified that the surface roughness of the work piece is significantly influenced by cutting parameters,and a mathematical model for predicting the surface roughness of the work piece can be constructed, as follow: Ra= 0,0102185 Vc + 8,81060 F + 8,5401 a – 0,0296552 Vc * a – 2,67699 Keywords: turning machined, surface roughness, cutting speed, feedrate, and depfth of cut. Abstrak Masalah terletak pada sulitnya memprediksi kekasaran permukaan hasil perautan menggunakan mesin bubut CNC, karena belum dimilikinya model matematik yang mengekspresikan pembentukan permukaan hasil proses perautan tersebut. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh parameter perautan terhadap kekasaran permukaan hasil perautan menggunakan mesin bubut CNC dan mendapatkan model matematik yang bisa digunakan untuk memprediksi keksaran permukaan bendakerja hasil perautan dengan data parameter yang digunakan. Cara uji meliputi: pemilihan bahan material uji, persiapan material uji, perautan material uji dengan data perautan yang ditetapkan, dan pengukuran kekasaran permukaan bendakerja hasil perautan. Hasil pengujian berupa kekasaran permukaan bendakerja untuk kombinasi kecepatan potong 62,8; 141; 219 meter per menit, kecepatan pemakanan 0,08; 0,34; 0,6 milimeter per putaran dan ketebalan penyayatan 0,3; 1,0; 2,0 milimeter. Pada akhirnya didapatkan hasil parameter perautan tersebut memiliki pengaruh terhadap kekasaran permukaan bendakerja sangat signifikan, serta didapat sebuah model matematik untuk memprediksi kekasaran permukaan bendakerja sebagai berikut: Ra= 0,0102185 Vc + 8,81060 F + 8,5401 a – 0,0296552 Vc * a – 2,67699 Kata kunci : mesin bubut, kekasaran permukaan, kecepatan potong, kecepatan pemakanan dan kedalaman penyayatan.